IMPLEMENTATION OF MINIMUM SERVICE STANDARDS POLICY AT THE REGIONAL PLANNING AND DEVELOPMENT AGENCY OF SANGGAU REGENCY - NIM. E1011151059, Irma Sri Wahyuni; *, Sugito; *, Deni Darmawan (PublikA, Jurnal Ilmu Administrasi Negara, 2019)
This undergraduate thesis research aims to provide an understanding of the Implementation of Minimum Service Standards Policy at the Regional Planning and Development Agency of Sanggau Regency, with a focus of research on factors that influence the Implementation of the Minimum Service Standards Policy at the qualitative research method and a descriptive approach. The location of this study was at the Regional Planning and Development Agency (BAPPEDA) of Sanggau Regency. In Implementing the Minimum Service Standars Policy at the Regional Planning and Development Agency of Sanggau Regency, seen from the theory by Van Meter and Van Horn, there are 6 (six) veriables that influence the Minimum Service Standars Policy, namely standars and objectives of the policy, Resources, Characteristics of implementing agencies, Attitudes / dispositions of implementers, Communicating between organizations and implementing activities, Social and political economic environment. The results of this study show that there is still a lack of quantity and quality of the resources of the planner apparatus in providing services as well as an understanding of the apparatus resources towards minimum service standard policy which is still inefficient due to the lack of internal coordination within the Regional Planning and Development Agency. Keywords: Implementation, Public Policy, Minimum Service Standars